2022
DOI: 10.3389/fped.2022.749107
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-RMST Functions as a Transcriptional Co-regulator of SOX2 to Regulate miR-1251 in the Progression of Hirschsprung's Disease

Abstract: Hirschsprung's disease (HSCR) is a congenital disorder characterized by the absence of enteric neural crest cells (ENCCs). LncRNA rhabdomyosarcoma 2-associated transcript (RMST) is essential for the growth and development of neuron. This study aimed to reveal the role of RMST in the pathogenesis of HSCR. The expression level of RMST, miR-1251, SOX2, and AHNAK was evaluated with qRT-PCR or western blot. CCK-8 and transwell assays were applied to detect cell proliferation and migration. CHIP and RIP assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For instance, dysregulation of lncRNA FAL1 and lncRNA LOC101926975 leads to cell cycle arrest at the G0/G1 phase [ 68 , 69 ], downregulation of lncRNA LINC00346 promotes cell apoptosis [ 16 ], and LncRNA HA117 may possess anti-differentiation functions [ 70 , 71 ]. Other lncRNAs, including MIR143HG, MEG3, LOC100507600, DRAIC, RMST, and ZFAS1 have also been detected to be aberrantly expressed in HSCR [ [72] , [73] , [74] , [75] , [76] , [77] ]. However, current research still has limitations, particularly in the lack of the ideal cell model ENCCs, which is the best model for exploring the pathogenesis of HSCR.…”
Section: Non-coding Rna Classes Associated With Hscrmentioning
confidence: 99%
“…For instance, dysregulation of lncRNA FAL1 and lncRNA LOC101926975 leads to cell cycle arrest at the G0/G1 phase [ 68 , 69 ], downregulation of lncRNA LINC00346 promotes cell apoptosis [ 16 ], and LncRNA HA117 may possess anti-differentiation functions [ 70 , 71 ]. Other lncRNAs, including MIR143HG, MEG3, LOC100507600, DRAIC, RMST, and ZFAS1 have also been detected to be aberrantly expressed in HSCR [ [72] , [73] , [74] , [75] , [76] , [77] ]. However, current research still has limitations, particularly in the lack of the ideal cell model ENCCs, which is the best model for exploring the pathogenesis of HSCR.…”
Section: Non-coding Rna Classes Associated With Hscrmentioning
confidence: 99%
“…The likelihood for other HMGB-RNA interactions is reinforced by prediction software which suggests the majority of Li, Zhu, et al, 2021) Sox1 (Hou et al, 2020) Unknown Sox2 (Hamilton et al, 2022;Holmes et al, 2020), (Cajigas et al, 2021;Hou et al, 2020;Tung et al, 2010) (Bai et al, 2022;Du et al, 2021;Guo et al, 2018;Jiang et al, 2018;Jing et al, 2020;Q. Li, Sun, et al, 2021;Ng et al, 2013;Ng et al, 2012;Samudyata, Amaral, et al, 2019;Stamou et al, 2020;Zhou et al, 2022;Zhuang et al, 2015) Sox4 Unknown (Chen et al, 2020) Sox6 (Hamilton et al, 2022) Unknown Sox9 (Hamilton et al, 2022) (Girardot et al, 2018;Pei et al, 2021;Penrad-Mobayed et al, 2018) Sox10 Unknown (Stamou et al, 2020) Sox11 (Hamilton et al, 2022) Unknown Sox13 (Yan et al, 2021) Unknown Sox15 (Hamilton et al, 2022) Unknown Sox17 (Hamilton et al, 2022) Unknown Sox21 (Hamilton et al, 2022) Unknown Sox30 (Hamilton et al, 2022) Unknown SRY (Hamilton et al, 2022) Unknown TCF7 (Lee & Jeong, 2004;Park et al, 2005) Unknown TFAM (Baltz et al, 2012;Brown et al, 2015;Castello et al, 2012Castello et al...…”
Section: Hmgbs Bind and Associate With Rnamentioning
confidence: 99%
“…From another study, Sox2 associates with RMST in neural crest cells and upon knockdown of RMST, Sox2's genomic localization was modified (Stamou et al, 2020). Another study identified a Sox2–RMST association which was thought to co‐regulate the expression of microRNA; however, the impact on localization was not explored (Zhou et al, 2022). The lncRNA, linc1548, also associates with Sox2 and upon knockdown of linc1548, Sox2's localization was lost at genes important for neuronal differentiation (Bai et al, 2022).…”
Section: Hmgbs Interactions With Rna Impact Hmgb Cell Biologymentioning
confidence: 99%
“…The same analysis allowed us to identify another lncRNA strongly downregulated in ATC, the rhabdomyosarcoma 2-associated transcript ( RMST ) [ 10 ]. RMST is a physiologic regulator of differentiation and stemness features of several tissues [ 12 , 13 ], furthermore it has been described to be deregulated [ 14 , 15 ] and to exert a critical tumor suppression role in cancer [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%